Impact of Life Experiences and Use of Web 2.0 Tools in Adults and Older Adults - Díaz-Prieto, Cristina; García-Sánchez, Jesús-Nicasio; Canedo-García, Alejandro (Frontiers in Psychology, 2019)
The aim of this study was to explore the relationship between favourable and stressful life experiences and perceived quality of life, practices that promote quality of life, psychological profiles and the daily use of web 2.0 tools in adults and older adults. An online questionnaire was designed, which was administered to 1095 Spanish adults and older adults, and conducted descriptive and multivariate analyses using the general linear model. Our results showed that favourable and stressful life experiences alike were associated with differential patterns in psychological profiles, perceived quality of life and daily activities and practices that affect quality of life, including the use of web 2.0 tools. Favourable life experiences mainly affected psychological profiles and the use of web 2.0 tools, whereas stressful life experiences affected the other factors analysed. Statistically significant differences were not found according to age and gender . These findings have important implications for promoting successful psychological and social interventions.